2013
DOI: 10.1016/j.bbi.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 primarily produced by non-hematopoietic cells mediates the lipopolysaccharide-induced febrile response

Abstract: KO background, but with intact IL-6 production in cells of hematopoietic origin, only showed a minor elevation of the body temperature after peripheral LPS injection. While they displayed significantly elevated levels of IL-6 both in plasma and CSF compared with control mice, the increase was modest compared with that seen in LPS injected mice on a WT background, the latter being approximately 20 times larger in magnitude. These results suggest that IL-6 of non-hematopoietic origin is the main source of IL-6 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 73 publications
0
21
0
1
Order By: Relevance
“…IL-6 is secreted by many cells, including fibroblasts, hepatocytes, endothelial cells, and, especially, adipocytes, in addition to leukocytes (Hamzic et al, 2013; Lepiller et al, 2013; Saiki et al, 2013; Salman et al, 2013). The diversity of these tissue sources is key to understanding the heritability of IL-6, especially given the strong genetic and familial influences on adiposity (Schousboe et al, 2003; Segal et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is secreted by many cells, including fibroblasts, hepatocytes, endothelial cells, and, especially, adipocytes, in addition to leukocytes (Hamzic et al, 2013; Lepiller et al, 2013; Saiki et al, 2013; Salman et al, 2013). The diversity of these tissue sources is key to understanding the heritability of IL-6, especially given the strong genetic and familial influences on adiposity (Schousboe et al, 2003; Segal et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Both IL1b and TNFa can induce the expression of each other (Dinarello et al, 1986;Ikejima et al, 1990) and are potent inducers of IL6 (Zetterstrom et al, 1998), which on contrary tends to be an inhibitor of IL1b and TNFa production (Netea et al, 2000;Schindler et al, 1990). IL6 seems to be the major mediator for sustaining fever; indeed, IL6-knockout mice or IL6-neutralizing antibodiesinjected mice were not able to develop LPS-induced fever, even if TNFa and IL1b upregulation was unaltered (Chai et al, 1996;Hamzic et al, 2013;Kozak et al, 1998).…”
Section: Exogenous and Endogenous Pyrogensmentioning
confidence: 99%
“…There may also be white-blood cells infiltration into the brain (Simard et al, 2006) and hippocampal dysfunction (Monje et al, 2002). Nonetheless, we and others have shown that the immune response both in the periphery and centrally (in the brain) are not compromised in chimeric mice, as measured by the release of cytokines like IL-1β (paper I) and IL-6 (Hamzic et al, 2013b) or by absence of white blood cell infiltration of the brain tissue (Turrin et al, 2007) (paper I).…”
Section: Mice Strainsmentioning
confidence: 99%
“…Two main opposing views emerged, one supporting the endothelial cells (Cao et al, 1995;Ek et al, 2001;Matsumura et al, 1998;Yamagata et al, 2001) and the other favoring the perivascular macrophages (Breder and Saper, 1996;Elmquist et al, 1997a;Schiltz and Sawchenko, 2002). To address this question, we (paper I) Hamzic et al, 2013b;Matsuwaki et al, 2014;Wilhelms et al, 2014) and other groups (Chakravarty and Herkenham, 2005;Ching et al, 2007;Gosselin and Rivest, 2008;Ridder et al, 2011) have developed complex transgenic mice models that allowed in vivo analysis of one gene in a BBB cell population at a time (reviewed with paper I).…”
Section: The Bbb As An Interface For Immune Signal-transductionmentioning
confidence: 99%
See 1 more Smart Citation